Aberrant iron metabolism might have an impact on progression of diseases in Tsumura Suzuki obese diabetes mice, a model of spontaneous metabolic syndrome. Issue 11 (29th September 2016) - Nishida, Takeshi; Tsuneyama, Koichi; Fujimoto, Makoto; Nomoto, Kazuhiro; Hayashi, Shinichi; Miwa, Shigeharu; Nakajima, Takahiko; Nakanishi, Yuko; Hatta, Hideki; Imura, Johji
Abstract: Tsumura Suzuki obese diabetes (TSOD) mice spontaneously develop obesity and type 2 diabetes with aberrant accumulation of excessive iron in the spleen. Aberrantly accumulated iron may cause oxidative stress and result in various symptoms of metabolic syndrome in the mice. We investigated iron metabolism and oxidative stress in TSOD mice. Male TSOD and control mice were killed at 2, 3, 6, and 8 months of age, and blood and tissue samples were collected. The serum levels of ferritin and oxidized low‐density lipoprotein (OxLDL) were measured. Total glutathione concentrations of liver and spleen were also measured. Serum ferritin and OxLDL were higher in TSOD mice than in control mice at 2 and 6 months. In addition, the glutathione concentrations in TSOD mice were lower in the liver and higher in the spleen at 3 and 6 months than those in control mice. These results suggest that abnormal iron metabolism and imbalanced oxidative stress occurs in young and old TSOD mice. We propose herein that TSOD mice might be a unique and valuable model for investigating the role of iron metabolism in pathogenesis of metabolic syndrome.